THE EFFECTIVENESS OF STORY GRAMMAR STRATEGYTO IMPROVE STUDENTS' READING COMPREHENSIONOF NARRATIVE TEXT(AN EXPERIMENTAL STUDY OF THE TENTH GRADE STUDENTS AT SMAN 9 BANDUNG) - Liana Savitri Supono, - (2009)
This paper is entitled "The Effectiveness of Story Grammar Strategy to Improve Students' Reading Comprehension of Narrative Text (An Experimental Study to the Tenth Grade Students of SMAN 9 Bandung)". This study was conducted by using quasi-experimental research. The population of this study was tenth grade students at SMAN 9 Bandung in which two classes were taken as the sample. They were X-6 and X-7 students. The data were gathered by administering pretest and posttest to both groups' sample. In addition, the questionnaire was conducted only for experimental group, in order to find out students' response towards the use of story grammar in teaching narrative text. The posttest result indicates that there were significant differences between means for experimental group and control group. It was statistically supported by t-test calculation in which the result shows that the null hypothesis was rejected. Furthermore, the questionnaire result indicates that there were positive responses that story grammar is effective. From the result, using story grammar is expected to be a strategy for helping teacher in teaching narrative text especially story.